Vibration suppression of flexible beam using eddy current damper - Hasan, Zainal Abidin (2013)
Eddy current damper undeniably has a vital role in absorbing vibration just like usual damper. This project is proposed to suppress the vibration of aluminum beam byelectromagnetic force of two different kind of copper coils, cylinder and squared coils. This project also focusing on investigating the vibration and damping characteristics of flexible beam itself. The eddy current damper is actually obtained from electromagnetic force which is produced by current flow in copper coil and helped by mild steel rod which functions to increase the magnetic field tremendously due to its high magnetic permeability. In order to measure the vibration produced on aluminium beam, DASYLAB software is used by the help of these two important materials which are accelerometer and DAQ component. From DASYLAB, the result for frequency response for each types of coil will be taken and converted into graph by using MATLAB software in order to get the clearest view for the comparison. The result will be analyzed based on the acceleration of the aluminium beam itself. Higher result of acceleration means higher result of vibration and vice versa. More of the detailed information can be referred to this thesis.